Разлике специфичне за пол у уклапању између два различита типа панцира: пилот студија - Buttner , Claire; Tiller, Sharne-Louise; Vollenweider , Nash; Canetti, Elisa F.D.; Schram, Ben; Давес, Јаи; Lockie, Robert; Orr, Robin M (NBP. Nauka, bezbednost, policija, 2024)
Introduction: Body armour, whilst improving wearer survivability, can negatively impact physical performance and increase injury risk. These impacts may differ between male and female personnel due to the generic design of armour systems. The aim of this study was to assess sex-specific differences in comfort when wearing military (MBA) and law enforcement (LEBA) body armour. Methods: Using a prospective, within-subjects, repeated measures, randomized cross-over design, 10 police officers (female=6: male=4) wore each set of body armour. After completing a variety of tasks, officers provided feedback on a subjective mannequin sketch and provided free text comments. Results: The heavier MBA received more negative comments than LEBA. The majority of negative comments by female officers referred to: (a) discomfort around the throat and shoulders, particularly when seated (six comments), (b) the vest compressing the utility belt or holster (six comments); (c) compression of the stomach and back (two comments); (d) restrictions in breathing and range of motion (four comments), (e) reduced ability to perform tasks (two comments); and (f) ill-fitting design (two comments). In comparison, male officers reported: (a) discomfort around the shoulders and abdomen (five comments), particularly when seated (three of the five comments); and (b) hip discomfort (e.g., pinching) (two comments). Conclusion: Comfort and fit of body armour should not be considered the same between males and females. Industries need to consider these sex-specific differences in their research and design. Agencies should investigate potential differences between sexes and between systems when purchasing such systems.
Keywords: Спровођење закона, полиција, војска, лична заштитна опрема, балистички прслук.